Hubungan Tingkat Kelelahan dan Beban Kerja dengan Kualitas Hidup Profesional Perawat di Rumah Sakit - Pratama, Julian Syaputra; Yulia, Sri; Romiko, Romiko (JKM : Jurnal Keperawatan Merdeka, 2024)
Introduction: The complex work environment and task responsibilities in hospitals play a major role in the personal aspects of staff, including fatigue and workload felt by nurses. Quality of Life Professional (QOL) of nurses is important to realize productivity and quality of service in hospitals. Objective: To analyze the relationship of fatigue level and workload with nurses' professional quality of life. Method: The research method used was cross sectional with purposive sampling technique of 44 nurse respondents from a private hospital in Palembang City. Data analysis used was Chi Square test. Results: The results of the study showed that the level of fatigue of nurses at the Muhammadiyah Hospital in Palembang was an average of 55.69, the majority of nurses' workload was in the medium category of 18 respondents (40.0%), and the quality of professional life of nurses was in the high category of 23 respondents (51.13%) with statistical results using the Chi Square test with a p value of 0.023 (p <0.05). Conclusion: Strategies are needed to optimize the management of nurses' fatigue levels and workload both personally and by institutions in order to support nurses' improved professional quality of life.